Tapering biologics in axial spondyloarthritis: A systematic literature review - Saoussen, Miladi; Yasmine, Makhlouf; Lilia, Nacef; Alia, Fazaa; Hiba, Bousaa; Kawther, Ben Abdelghani; Ahmed, Laatar (International immunopharmacology, 2022)
•Tapering the anti-TNF α among ax-SpA patients in sustained remission was not related to disease flare.•Tapering biologics doses in a slowly manner is recommended.•Stopping biologics in ax-SpA in remission is not recommended. The emergence of biologics has improved the management of patients with rheumatic disease, mainly with spondyloarthritis (SpA). Sustained remission has become a reachable goal thanks to the treat to target strategy. Contrary to rheumatoid arthritis, data on biologic optimization among SpA patients in remission is scarce and still a subject of debate. The main objective of this systematic review was to provide the most up-to-date published literature regarding biologic tapering in axial spondyloarthritis. This systematic review followed the preferred reporting items for systematic reviews guidelines. Original articles from Pubmed and Scopus, published until December 20th 2021, and tackling tapering strategies of the biologics in patients with axial SpA were included Fourteen studies met the inclusion criteria. They were published between 2008 and 2020. The most studied molecules were Etanercept (ETN) (n = 13), Infliximab (IFX) (n = 6), Adalimumab (ADA) (n = 5), certolizumab pegol (CZP) (n = 2), Golimumab (n = 1) and ETN biosimilar. There are no studies published regarding anti-IL 17 tapering strategy. Patient-tailored dose reduction of anti TNF-α agents was successful in preserving stable low disease activity in most of the studies with remission rates ranging between 20.2 % and 93.7 %. Complete treatment discontinuation is associated with a high risk of flares. To conclude, published data indicate that a progressive tapering strategy for anti TNF-α therapy is successful among axial SpA in sustained remission. However, further studies with more homogenized tapering strategies are needed in order to ascertain the specific implication of each subset for a better holistic approach.